2018
DOI: 10.1371/journal.pone.0201894
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and prevalence of dysmenorrhea among Spanish female university students

Abstract: The aim of this study was to determine the prevalence of primary dysmenorrhea in a sample of Spanish university students, and to describe their menstrual characteristics, lifestyle habits and associated risk factors. This cross-sectional study was conducted with a total of 258 young female university students recruited from the Ciudad Real Faculty of Nursing, with a mean age of 20.63± 3.32 years. An anonymous self-report questionnaire was used to collect data from students. This included sociodemographic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
125
5
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(158 citation statements)
references
References 39 publications
18
125
5
10
Order By: Relevance
“…The common symptoms associated with PD identified in this study were lower abdominal pain (85.9%), fatigue (60.9%), and irritability (50.8%), which are similar to those in a study among Spanish female university students. That study indicated edema (92.7%), irritability (81.9%), and fatigue (79.3%) as common symptoms, 27 although irritability and fatigue were more common than observed in this study. Similarly, the symptoms observed in this study are comparable with those in a study performed among Mexican university students in which the major symptoms associated with dysmenorrhea were lower abdominal pain (93%), irritability (50%), and depression (48%).…”
Section: Discussioncontrasting
confidence: 60%
“…The common symptoms associated with PD identified in this study were lower abdominal pain (85.9%), fatigue (60.9%), and irritability (50.8%), which are similar to those in a study among Spanish female university students. That study indicated edema (92.7%), irritability (81.9%), and fatigue (79.3%) as common symptoms, 27 although irritability and fatigue were more common than observed in this study. Similarly, the symptoms observed in this study are comparable with those in a study performed among Mexican university students in which the major symptoms associated with dysmenorrhea were lower abdominal pain (93%), irritability (50%), and depression (48%).…”
Section: Discussioncontrasting
confidence: 60%
“…The methodological quality of cross-sectional studies was assessed using the tool, the Agency for Healthcare Research and Quality (AHRQ). Studies assessed using this tool are classified as high quality (if they scored [8][9][10][11], moderate quality (if they scored 4-7) or low quality (if they scored 0-3). The methodological quality of cohort or case-control studies was assessed using the New-Ottawa Scale (NOS).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Cigarette smoking has been reported in literature as one of the modifiable risk factors for dysmenorrhea. Although women who smoke reported a range of more adverse reproductive outcomes than their non-smoking counterparts, the relationship between smoking and dysmenorrhea is still heterogeneous [11,12]. That is, some studies found that smokers were more likely to experience dysmenorrhea than non-smokers, whereas other studies reported that smokers were less likely to experience dysmenorrhea than non-smokers, and another study showed that smoking had no effect on dysmenorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies indicated that several factors affecting the intensity of menstrual pain were young menarche age, longer menstrual duration and excess menstrual volume 9,[26][27][28] . The intensity of menstrual pain could be mild, moderate and severe 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The dysmenorrhea prevalence in the world is reported high and varied. The incidence of dysmenorrhea in female students at the An-Najah Palestine National University was 846 (85.1%) of the 956 female students who experienced menstruation 8 , at Castilla-La-Mancha University in Spain, the incidence of dysmenorrhea was 74.8% from 193 female students 9 and in India the incidence of dysmenorrhea in adolescents was 73.9% 10 . The incidence of dysmenorrhea in Indonesia was also high compared to other countries in the world, estimated at around 64.25% 11 with the percentage of primary dysmenorrhea of 90% and secondary dysmenorrhea of 15% 12 .…”
Section: Introductionmentioning
confidence: 96%